Influence of high expansion dental stone used as investing medium on the changes in occlusal vertical dimension of complete dentures - Alaa’a M. Salloum (Saudi Dental Journal)
Problem statement: Despite advances in materials and techniques, complete dentures made of acrylic resin experience an increase in the occlusal vertical dimension (OVD) during processing. Many factors that affect the OVD of complete dentures are known. However, no study has examined the effect of using high-expansion dental stone (type V) as an investing material on the OVD. Purpose: This study investigated the effects of using a high-expansion dental stone as an investing material on changes in the OVD of complete dentures. Material and methods: Twenty sets of simulated upper and lower dentures were processed by the compression molding technique. Specimens were equally divided into 2 groups. In the dental stone type III (DST III) group, the lower, middle, and upper parts of a flask were filled with DST III. In the dental stone type V (DST V) group, the procedure was the same as in the DST III group, except that the middle layer was made of high-expansion DST V. Changes in the OVD were measured before and after denture processing. Collected data were analyzed with t-test statistics. Differences were considered statistically significant at the 95% confidence level. Results: Both groups showed a small increase in the OVD as a result of processing, but the OVD increase was significantly less in the DST V group compared to the DST III group. Conclusion: High-expansion DST V can be recommended as an investing material to reduce the increase in the OVD that may occur while processing complete dentures. Keywords: Acrylic resin, Complete denture, Denture base, High expansion dental stone, Investing, Occlusal vertical dimension